Structural insights into RNA encapsidation and helical assembly of the Toscana virus nucleoprotein. Issue 9 (31st March 2014) - Olal, Daniel; Dick, Alexej; Woods, Virgil L.; Liu, Tong; Li, Sheng; Devignot, Stephanie; Weber, Friedemann; Saphire, Erica Ollmann; Daumke, Oliver
Abstract: Toscana virus is an emerging bunyavirus in Mediterranean Europe where it accounts for 80% of pediatric meningitis cases during the summer. The negative-strand ribonucleic acid (RNA) genome of the virus is wrapped around the virally encoded nucleoprotein N to form the ribonucleoprotein complex (RNP). We determined crystal structures of hexameric N alone (apo) and in complex with a nonameric single-stranded RNA. RNA is sequestered in a sequence-independent fashion in a deep groove inside the hexamer. At the junction between two adjacent copies of Ns, RNA binding induced an inter-subunit rotation, which opened the RNA-binding tunnel and created a new assembly interface at the outside of the hexamer. Based on these findings, we suggest a structural model for how binding of RNA to N promotes the formation of helical RNPs, which are a characteristic hallmark of many negative-strand RNA viruses.